Medical students’ experiential learning on social determinants of health: a constructivist qualitative study - Ge, Yurong; Ariga, Makie; Takeda, Yuko (BMC medical education, 2025)
Background In addressing health disparities, it is crucial to train doctors who can understand the social contexts of their patients. While experiential learning has been shown to enhance medical students’ understanding of Social Determinants of Health (SDH), few studies have examined its impact on students’ cognitive, emotional, and personal growth. This study aims to explore how experiential learning influences medical students’ understanding of SDH and fosters growth in cognition, emotion, and social responsibility. Methods Since 2015, an 8-week elective course at Juntendo University School of Medicine has aimed to help third-year students understand SDH through direct engagement with marginalized groups. Using a constructivist thematic analysis approach, we analyzed reports from 33 students and collaborative videos from 2015 to 2021. Results The analysis revealed five key themes: (1) Awareness of social issues, (2) Changes in personal perspectives, (3) A deeper understanding of SDH, (4) Exploration of future roles and actions, and (5) Personal growth through experiential learning and reflection. Conclusion Experiential learning led to significant emotional and cognitive shifts, enhancing students’ understanding of how social factors affect health and strengthening their sense of social responsibility. However, students also expressed complex emotional reactions to social inequalities. Future research should explore how to convert these insights into long-term behavioral changes and enhance the integration of reflection and collaborative learning in medical education.